2018
DOI: 10.1039/c8ta06304d
|View full text |Cite
|
Sign up to set email alerts
|

A Cu3P nanowire enabling high-efficiency, reliable, and energy-efficient low-voltage electroporation-inactivation of pathogens in water

Abstract: A Cu3PNW–Cu electrode serves as an efficient and stable electrode for low-voltage electroporation-inactivation of pathogens in water with high energy efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…Fisher et al reported fabrication of nanocone-shaped diamond on silicon substrate and observed cell membrane damages and bacteria lysis [46]. Other nanowire-modified antimicrobial filters based Ag+-induced bacterial inactivation or electroporation-inactivation also resulted in bacterial morphological changes [47, 48]. Our LEO- and TTO- MWCNTs filters showed much more severe damages on captured bacteria than the antimicrobial surfaces from these literatures, especially our TTO(50 μL)-MWCNTs filters, which damaged all the captured bacteria and showed 100% inhibitory rates.…”
Section: Resultsmentioning
confidence: 99%
“…Fisher et al reported fabrication of nanocone-shaped diamond on silicon substrate and observed cell membrane damages and bacteria lysis [46]. Other nanowire-modified antimicrobial filters based Ag+-induced bacterial inactivation or electroporation-inactivation also resulted in bacterial morphological changes [47, 48]. Our LEO- and TTO- MWCNTs filters showed much more severe damages on captured bacteria than the antimicrobial surfaces from these literatures, especially our TTO(50 μL)-MWCNTs filters, which damaged all the captured bacteria and showed 100% inhibitory rates.…”
Section: Resultsmentioning
confidence: 99%
“…In this expression, the time constant τ is given by τ = rC m (ρ int + ρ ext /2), where C m is the membrane capacitance and ρ int and ρ ext are the resistivities of the cytoplasm and external medium, respectively. It is observed that if the frequency is high (>10 4 Hz), the TMP is reduced and the duration of the electric field becomes too short to charge the membrane, thereby causing a reduction in electroporation [16,53]. At higher frequencies, the log removal may be due to the cell DEP effect resulting from insulating beads inducing a nonuniform electric field.…”
Section: Effect Of Ac Frequencymentioning
confidence: 99%
“…It also plays an important role in recent breakthroughs such as gene editing (CRISPR-Cas9) [8,9] and cell reprogramming (induced neurons) [10]. Moreover, this method is used in the beverage, wine, and dairy industries for disinfecting liquid products [11][12][13][14] and shows great potential in the field of water treatment as well [15][16][17]. However, to maintain the high electric field strength required for electroporation, electric voltages up to 10 5 volts are usually employed, which increases the issues concerning operational safety.…”
Section: Introductionmentioning
confidence: 99%
“…To generate highly localized electric elds, nanowires (e.g., Ag, CuO, and ZnO nanowires) are placed vertically on a at electrode surface to enhance the eld at the wire tip signi cantly (>10 7 V m -1 ) using only low drive voltages (several V) 17,18,19 . In fact, a nanowire-assisted electroporation disinfection technology has recently been con rmed as feasible for bacterial disinfection in water 20,21 . However, due to the enhanced electric eld only existing near the nanowire tip, unless the microbes approach the tip structure, disinfection won't occur.…”
Section: Introductionmentioning
confidence: 99%